Analytical and experimental studies for power-law fluids in a double-pass parallel-plate heat exchanger under asymmetric isotherm conditions. (March 2017) - Ho, Chii-Dong; Lin, Gwo-Geng; Lin, Cheng-Yi; Jen, Li-Yang
Highlights: Recycling double-pass parallel-plate heat exchanger for power-law fluids. The problems with asymmetric isotherm conditions are investigated analytically. The heat-transfer efficiency enhancement was obtained. Abstract: The double-pass parallel-plate heat exchanger under asymmetric isotherm conditions referred to conjugated Graetz problem was proposed to enhance the thermal performance and investigated theoretically and experimentally. The analytical solutions were obtained using the separation of variables, superposition principle and an orthogonal expansion technique in terms of power series. The dependence of the average Nusselt number on the Graetz number and power-law index was formulated in a simplified expression. The theoretical predictions show that the power-law fluids in such a double-pass operation come up with the considerable heat-transfer efficiency improvement as compared with those in an open conduit (without an impermeable resistless sheet inserted), especially when the double-pass device was operated in larger Graetz numbers. This work shows that the good agreement was obtained between the experimental results and theoretical predictions. The effects of the ratio of asymmetric wall temperatures, impermeable-sheet position and power-law index on both the device performance enhancement and power consumption increment have also been presented.